SEJARAH PEMIKIRAN HUKUM AHMAD BIN HANBAL - Husnul Khatimah (LP2M Universitas Ibrahimy, 2017)
Imam Ahmad bin Hanbal is the fourth Imam of the fuqoha 'Islam. Descendants of Ahmad bin Hanbal met with the descendants of Rasulullah SAW on Mazin bin Mu'ad bin 'Adnan. Ahmad bin Hanbal was born in Baghdad Rabiul Awwal 164 H / 780 AD He is a figure of a character who has noble character, high character, simple, populist and has high Islamic commitment. His love of hadith and allegiance to Prophet Muhammad SAW to be paid with physical and non-physical sacrifices is an added value to be respected. In addition to hadith and fiqh experts, he is a productive scientist, it is seen from some of his works that we can still find today. His famous book is Musnad, which is one of the most important and valuable heritages for formulation of contemporary thought and problem solving. Book of Musnad is also one of the most widely read references to date. Method of writing this book is based on names of companions of the Prophet who narrated the hadith. To Consider the Qur'an as a source of Islamic law, Ahmad ibn Hanbal argues that the Qur'an is a fundamental source of Islam, followed by sunnah, but according to him as Sunnah has a position that is equally strong in addition to the Qur'an. In interpretation of Qur'anic verse, Imam Ahmad really attaches importance to interpretation that comes from sunnah.